EFFECTS OF CONTROLLING HYPERTENSION PROGRAMS ACCORDING TO HEALTH BELIEFS CONCEPT AFFECTING CONTROLLING HYPERTENSION BEHAVIORS OF THE PATIENTS AT HEALTH PROMOTING HOSPITAL IN PLUAKDAENG DISTRICT RAYONG PROVINCE - พงษ์พิทักษ์, พรรณธิดา; วัฒนบุรานนท์, เอมอัชฌา (Primary Health Care Journal (Northeastern Edition), 2025)
Hypertension is a major public health concern worldwide, including in Thailand. Without proper treatment and lifestyle modification, individuals with hypertension face a twofold increased risk of myocardial infarction and a fourfold increased risk of stroke. This quasi-experimental study aimed to examine the effects of a hypertension control program, based on the Health Belief Model, on self-care behaviors among hypertensive patients in a sub-district health-promoting hospital in Pluak Daeng District, Rayong Province. The sample consisted of 64 hypertensive patients, divided into an experimental group (n = 32) and a control group (n = 32). The experimental group received the hypertension control program over a six-week period. Data were collected using questionnaires and analyzed with descriptive statistics and inferential statistics, including paired samples t-test, independent samples t-test, and repeated measures ANOVA. The results revealed that, after the intervention, the experimental group showed a statistically significant improvement in overall self-care behavior scores compared to both baseline and the control group (p < 0.001). Regarding blood pressure control, the experimental group demonstrated a significant reduction in mean blood pressure from 146.19/93.56 mmHg before the intervention to 130.22/79.53 mmHg after the intervention, and further to 129.53/77.94 mmHg during follow-up (p < 0.001). The findings indicate that the behavioral modification program was effective in promoting appropriate health behaviors and in reducing blood pressure among hypertensive patients.